Formation and neutralization of electric charge and current of an ion thruster plume. (27th October 2021) - Perales-Díaz, Jesús; Cichocki, Filippo; Merino, Mario; Ahedo, Eduardo
Abstract: A 3D hybrid model is introduced and applied to the simulation of the xenon plasma plume extraction, formation, and neutralization in a gridded ion thruster. The acceleration voltage is 1100 V and the inflow Xe + per hole ranges from 0.07 to 0.92 μ g s −1 . While ions and neutrals are treated with a particle-in-cell formulation, electrons are modeled as two independent isothermal populations: one inside the discharge chamber and one in the plume. The definition of a thermalized potential allows to solve the electron currents in the high-conductivity limit of the Ohm's law. The space charge neutralization distance is observed to be short and thus essentially independent of the acceleration grid-neutralizer distance, which is varied from 10 to 25 mm axially. However, this position strongly affects the electric current neutralization paths in the near plume for each ion beamlet. Electron inertial forces are shown to be comparable to collisional forces in certain plasma regions. A semi-analytical 1D fluid model of the plume, matched to the hybrid model, allows to complete the far plume expansion down to infinity. Grids with an infinite and finite number of apertures are simulated and compared with each other and with the 1D model. The numerically obtained divergence angle of the ion plume is compared with experimental measurements, observing relative errors of around 7% in the position of the optimal perveance, and smaller than 4% in the divergence angle average value.